WHY MUST TANOÉ-EHY FOREST (SOUTHEASTERN CÔTE D‟IVOIRE) BE CONSERVED WITH A COMMUNITY-BASED APPROACH? - Armand Zadou, Didié (European Scientific Journal, ESJ, 2014)
The Tanoé-Ehy Forest was identified as a top priority site forconservation in West Africa. However, this important forest is subject tostrong anthropogenic pressures which through poaching, uncontrolled takeoffs of natural resources and some agricultural clearings. Given theimportance of this forest and the intensity of threats, a pilot program forcommunity-based management was initiated with people living alongsideTanoé-Ehy Forest for sustainable management of this forest. Since the usualmethods for forest management by the government don‘t often privilege theinterests of local people, the main concern for this contribution is why mustthis forest be conserved with a community-based approach? This qualitativestudy demonstrates how local context is important to determine conservationpolicy, through an exploration of the importance of Tanoé-Ehy Forest to themaintenance of cultural references in this area, and local uses and users ofthe derivatives of this forest. In sum, we can say that Tanoé-Ehy Forest is avital heritage for local populations dependent on natural resources forsubsistence. Community-based sustainable management of Tanoé-EhyForest benefits autochthons, allochthons and foreigners. Thus, taking intoaccount their interests in the conservation program of this forest is crucial.